2019
DOI: 10.3168/jds.2018-15906
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes associated with the heritable humoral response to Mycobacterium avium ssp. paratuberculosis in dairy cows have factors in common with gastrointestinal diseases in humans

Abstract: Infection of cattle with bovine paratuberculosis (i.e., Johne's disease) is caused by Mycobacterium avium ssp. paratuberculosis (MAP) and results in a chronic incurable gastroenteritis. This disease, which has economic ramifications for the cattle industry, is increasing in detected prevalence globally; subclinically infected animals can silently shed the bacterium into the environment for years, exposing contemporaries and hampering disease-control programs. The objective of the present study was to first qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Research into MAP virulence is rooted in the desire to understand pathophysiological effects of MAP in different life forms and to establish clinical and subclinical biomarkers of MAP infections and diseases. These researches seek to determine molecular resistance, susceptibility gene markers or factors that drive the establishment of MAP infections in hosts [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Growth related to MAP disease resistance research underscored the inclination towards selection of animal breeding stocks that are capable of high productivity in the event of MAP infections on-farm to minimize husbandry failures and economic losses.…”
Section: Resultsmentioning
confidence: 99%
“…Research into MAP virulence is rooted in the desire to understand pathophysiological effects of MAP in different life forms and to establish clinical and subclinical biomarkers of MAP infections and diseases. These researches seek to determine molecular resistance, susceptibility gene markers or factors that drive the establishment of MAP infections in hosts [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Growth related to MAP disease resistance research underscored the inclination towards selection of animal breeding stocks that are capable of high productivity in the event of MAP infections on-farm to minimize husbandry failures and economic losses.…”
Section: Resultsmentioning
confidence: 99%
“…Individual diagnostic tests for paratuberculosis are known to lack sensitivity and specificity, and these characteristics have been put forward as explanations for the low heritability of MAP-related traits that has been reported in the literature. Since the study of Settles et al in 2009 [9] to the most recent publication in 2019, 13 GWAS analyses have been conducted for traits linked with bovine paratuberculosis [6][7][8][9][10][11][12][13][14][15][16][17][18]. These studies examined various numbers of animals and SNPs, and all succeeded in identifying genomic regions associated with MAP resistance/susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous GWAS analyses have reported QTL on BTA23 that are associated with resistance to MAP, in the vicinity of the MHC [7-9, 16, 18], while only one previous study, a meta-analysis conducted in US Holsteins based on 50 K SNP genotypes, found QTL at ~ 70 Mbp on BTA12 and ~ 65 Mbp on BTA13 [8]. McGovern et al [18], who performed a GWAS on imputed whole-genome sequences, identified two SNPs associated with the humoral response to MAP on BTA13, at 62,037,755 bp and 66,373,805 bp, i.e. on either side of but quite far from the QTL we detected (63,497,960-63,506,532 bp) and outside its confidence interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs with SNPs in LRCH3 are more susceptible to infections with Escherichia coli (E. coli) and cows with SNPs in LRCH3 have a higher susceptibility to Mycobacterium avium ssp. paratuberculosis infection (Jacobsen et al, 2010;McGovern et al, 2019). Furthermore, gene amplifications of LRCH2 and LRCH3 are associated with tumorigenesis of low grade gliomas and melanomas, respectively (Liu et al, 2019;Williams et al, 2020).…”
Section: Genomic Analysesmentioning
confidence: 99%